When Does Digital Transformation Pay Off? Cost Channels and Heterogeneity in Chinese Manufacturing Firms - Chen, Baodong; Zhang, Jiayi (Asia Pacific Economic and Management Review, 2026)
Digital transformation serves as a key driver of better firm financial performance and a critical enabler of high-quality economic and social development. Using a panel dataset of Chinese A-share listed manufacturing firms over the 2011–2022 period, this study empirically examines how digital transformation affects firm financial performance, along with its transmission mechanisms and heterogeneous effects. We find that digital transformation significantly improves the financial performance of manufacturing enterprises. Mechanism tests show that digital transformation enhances performance by reducing transaction costs, while the mediating channel through production costs is not supported. Heterogeneity analysis further indicates that the positive performance effect of digital transformation is more pronounced among state-owned enterprises and mature firms. Our findings enrich the literature on digital transformation and firm performance, and provide empirical implications for corporate digital practices and public policies aimed at high-quality development.